Increasing Indonesian Students’ Writing Ability Through Make A Match Learning Model - Andi Hamsiah; Asdar; Asia M (Jurnal Pendidikan dan Pengajaran, 2023)
Nowdays in elementary and middle school, there has been a noticeable rise in expectations for children' writing abilities. This study aimed to analyze the application of make and match model on the writing skills of Indonesian students. The type of research used was experimental research, with a one group pretest-posttest design. The population of this study was fourth grade students, totaling 27 students, consisting of 13 students from class A and 14 students from class B. Data collection techniques in conducting this research are observation, tests, and documentation. Data analysis techniques use descriptive analysis and inferential analysis. Based on the results of the study obtained an average pretest score of 68.21 and posttest 78.85. The results obtained from the t-test, the t-count value is 8.034 and the t-table is 1.782 with a significant level of 0.05 turns out to meet the criteria, t-count t table. The data obtained by using the –t test formula. Based on the results of the study, it was obtained that the calculated data value was > from t table. Therefore, it can be concluded that the use of the make a match learning method is effective in learning Indonesian for improvement of the writing ability of the fourth grade students.